2003
DOI: 10.1017/s1092852900019003
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Electroconvulsive Therapy and Magnetic Seizure Therapy

Abstract: New findings regarding the mechanisms of action of electroconvulsive therapy (ECT) have led to novel developments in treatment technique to further improve this highly effective treatment for major depression. These new approaches include novel electrode placements, optimization of electrical stimulus parameters, and new methods for inducing more targeted seizures (eg, magnetic seizure therapy [MST]). MST is the use of transcranial magnetic stimulation to induce a seizure. Magnetic fields pass through tissue u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 65 publications
0
29
0
5
Order By: Relevance
“…In a recent randomised, double-blind trial 10 patients had significantly fewer and less severe muscle aches, subjective memory complaints and headaches. MST was in this trial also associated with faster recovery of orientation, and was superior to ECT on measures of attention, retrograde amnesia, and category fluency (Lisanby et al 2001;Burt et al 2002;Lisanby et al 2003;Kosel et al 2003).…”
Section: Meta-analysesmentioning
confidence: 67%
“…In a recent randomised, double-blind trial 10 patients had significantly fewer and less severe muscle aches, subjective memory complaints and headaches. MST was in this trial also associated with faster recovery of orientation, and was superior to ECT on measures of attention, retrograde amnesia, and category fluency (Lisanby et al 2001;Burt et al 2002;Lisanby et al 2003;Kosel et al 2003).…”
Section: Meta-analysesmentioning
confidence: 67%
“…Preclinical studies have demonstrated that rTMS modulates neural circuits and neurotransmitter systems such as dopamine and serotonin [40]. rTMS applied with conventional coils at the DLFPC region modulates cortical b-adrenergic receptors, decreases 5-HT 2 and increases 5-HT 1a serotonergic receptors in the frontal cortex and the ACC [41].…”
Section: Pathophysiological Considerationsmentioning
confidence: 99%
“…Instead, a coil placed on the head is used to generate high frequency, high intensity transcranial magnetic stimulation. Magnetic fi elds pass through the scalp and skull without the impedance affecting electric currents leading to depolarization of neurons in specifi c regions of the superfi cial cortex, which causes focal induction of a generalized seizure (Hoy & Fitzgerald, 2010aLisanby et al, 2003b). The aim is to target specifi c regions and circuits in the brain which are implicated in the pathogenesis of depression, without impinging on deeper, e.g.…”
Section: What Is the Difference Between Mst And Ect?mentioning
confidence: 99%